2020
DOI: 10.2807/1560-7917.es.2020.25.46.2001815
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of carbapenem-resistant ST131 Escherichia coli carrying blaOXA-244 in Germany, 2019 to 2020

Abstract: The dissemination of carbapenem-producing Gram-negative bacteria is a major public health concern. We report the first detection of OXA-244-producing ST131 O16:H5 Escherichia coli in three patients from two tertiary hospitals in the south-west of Germany. OXA-244 is emerging in Europe. Because of detection challenges, OXA-244-producing E. coli may be under-reported. The emergence of carbapenem resistance in a globally circulating high-risk clone, such as ST131 E. coli is of clinical relevance and should be mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…32 Worryingly, carbapenemase-producing E coli ST131 (mostly bla KPC and bla OXA-48-like ) have recently been reported from England and Germany. 33,34 In our study, ST131 strain H30R was most common, carrying predominantly bla CTX-M-14 and bla CTX-M-27 (ie, H30R1), whereas bla CTX-M-15 (associated with H30Rx strains) was less common. 25 Indeed, ST131 carrying bla CTX-M-27 has been suggested to be more transmissible than those with bla CTX-M-15 , which might explain its successful spread.…”
Section: Discussionmentioning
confidence: 53%
“…32 Worryingly, carbapenemase-producing E coli ST131 (mostly bla KPC and bla OXA-48-like ) have recently been reported from England and Germany. 33,34 In our study, ST131 strain H30R was most common, carrying predominantly bla CTX-M-14 and bla CTX-M-27 (ie, H30R1), whereas bla CTX-M-15 (associated with H30Rx strains) was less common. 25 Indeed, ST131 carrying bla CTX-M-27 has been suggested to be more transmissible than those with bla CTX-M-15 , which might explain its successful spread.…”
Section: Discussionmentioning
confidence: 53%
“…The persistence of certain E. coli clones, sporadically carrying carbapenemases genes, warrants further careful surveillance. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…The STs most frequently associated with carbapenemases in K. pneumoniae are ST258, which is predominant worldwide [ 8 ], and ST307, which is also associated with a higher mortality [ 9 ]. In Germany, it was reported that E. coli ST131 is a high-risk clone that should be monitored very closely [ 10 ], alongside ST38, located in various European countries [ 10 ]. In Spain, the STs most frequently associated with carbapenemases are ST11, 13, 15, 16, 101, 147, 340, 384, 388, 405, 437, 464, 512, 846 and 1235 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%